Hormonal activity and performance of ski-racers - Bakhareva, A.; Isaev, A. P.; Aminov, A. S.; Melnikova, O. V. (Journal of Physical Education and Sport, 2019)
The purpose of the article is to study the dynamics of hormonal activity in ski-racers in the preparatory and competitive period and to establish significant changes that demonstrate the effectiveness of competitive activity. Changes in testosterone, urine estrogens, T4 tyrosine and cortisol were compared in racers under training conditions of alternating middle altitude hypoxia and normoxia (group 1) and only normoxia (group 2). Materials and methods. 17 male ski-racers aged 18-23 years were involved in the study. The first group (1) consisted of cross-country skiers with a training process in the conditions of alternating middle altitude hypoxia (May-August-October) and normoxia (n = 7); the second group - ski-racers with the training process only in conditions of normoxia (n = 10). The study was conducted in the preparatory and competitive period (July and December). The cortisol content was determined using fluorometry with the help of Fluorat-02 ABLFT biofluid analyzer (Lumex, St. Petersburg, Russia) at a fluorescence excitation wavelength of 405 nm and an emission of 546 nm. At the same time, the object of laboratory research was heparinized blood taken from a cubital vein in the morning, on an empty stomach. The levels of total testosterone, urine estrogens, and T4 tyrosine were obtained with the help of a non-invasive AMP blood analyzer (Ukraine). Discriminant analysis was applied for statistical data processing as well as rank correlation analysis and nonparametric analysis of variance (William R. Kleck (1986). Results. It was found that in the 1st group of athletes there was an increase in total testosterone by 11.05% (p> 0.05), a decrease in urine estrogen and cortisol by 17.55% (p <0.05) and 29.91% (p <0.05), respectively. In the 2nd group, by the competitive period, we detected a decrease in testosterone by 6.41% (p> 0.05), urine estrogen by 3.49% (p> 0.05), tyrosine T4 by 0.18% (p> 0 , 05) against the background of an increase in the concentration of cortisol by 25.85% (p <0.05). Conclusion. The study showed that people with a combined training process have a more successful competitive activity. The nature of the responses in the process of adaptation is determined by a decrease in catabolic and an increase in anabolic processes. Key words: cross-country skiers, testosterone, cortisol, estrogens, T4 tyrosine, hypoxia, normoxia.